Quality of life related to age and economic income in diabetic older adults. Chillan, Chile, 2019 - David Isaac Caamaño Valderrama; Claudia Andrea Concha Navarro; Yocelin Belén Del Canto Celis; Gustavo Alberto Dupré Orias; Ismael Morales Ojeda; Paulina Segura Hernández (Medisur)
Background: suffering from diabetes can influence the perception of the individual himself and change his daily routine, thus affecting his quality of life; Based on this, the deepening of the subject is of great importance. Objective: to determine the relationship between quality of life, age and income in older adults with type 2 diabetes mellitus. Methods: a descriptive, cross-sectional study was carried out in 33 older adults with type 2 diabetes mellitus, selected by non-probabilistic convenience sampling, in the Las Mariposas community (Chillán, Chile), in 2019. The Diabetes 39 instrument was applied for quality of life analysis. The Kolmogorov-Smirnov and Spearman's Rho statistical tests were used. Results: the female sex was the predominant, as well as married people. Age had a mean value of 71.45 years. In the economic income, 66.7% of the participants reported the impossibility of paying the expenses of the month. Among the life’s quality dimensions analyzed, the most affected were: diabetes severity (mean 55.05), energy/mobility (mean 44.1), and quality of life (mean 43.9). Age and income did not show a significant correlation with any of the dimensions studied. Conclusions: the older adults’ quality of life with type 2 diabetes mellitus is affected, without a significant relationship with age and economic income.